Weighted average of viscous and drag resistance models with and without matching parameters for estimating hydraulic conductivity of soils - SINGH, SITA RAM; VERMA, CHHEDI LAL; SINGH, ATUL KUMAR (Journal of Soil and Water Conservation, 2020)
Hydraulic conductivity is the most important property of the granular porous materials and required for designing of drip irrigation system, ground water extraction and recharge structures and subsurface drainage systems. Hydraulic conductivity is also required for the management of ground water basins, movement of pollutants in soil and aquifer, infiltration and evaporation processes at the land surface, and water and nutrient uptake from soil profile by plant roots. Mathematical relationships have been developed using viscous and drag resistance models for describing the medium. Viscous and drag resistance models have been developed to estimate saturated hydraulic conductivity from particle size distribution and related properties of the media. Empirical equations for the matching parameters in the viscous and the drag resistance models based on measurable soil properties have been conjectured to improve the model’s accuracy. Weighted average hydraulic conductivities calculated by the two models with and without matching parameters were also evaluated for improving the estimate of hydraulic conductivity. Empirical equations for the matching parameters of the viscous and drag resistance models were developed using the measured and computed hydraulic conductivities of 75 UNSODA soils. The incorporation of the matching parameter Cv in the viscous resistance model has reduced the root mean square deviation (RMSD) between the computed and observed hydraulic conductivities of 75 UNSODA soils from 269.51 cm/day to 259.84 cm/day and that for drag resistance model from 325.27 cm/day to 298.11 cm/ day. Viscous resistance yielded better estimates of the saturated hydraulic conductivity than the drag resistance model. The closest values of RMSD of Ka further reduced for the weighted average model. Weighted average of the viscous and drag resistance models without the matching parameters (Ka = 0.72 Kv + 0.28 Kd ) yielded the best estimate of the saturated hydraulic conductivity.